Regioselective synthesis of heterocyclic N-sulfonyl amidines from heteroaromatic thioamides and sulfonyl azides - Ilkin, Vladimir; Berseneva, Vera; Beryozkina, Tetyana; Glukhareva, Tatiana; Dianova, Lidia; Dehaen, Wim; Seliverstova, Eugenia; Bakulev, Vasiliy (Beilstein Journal of Organic Chemistry, 2020)
N-Sulfonyl amidines bearing 1,2,3-triazole, isoxazole, thiazole and pyridine substituents were successfully prepared for the first time by reactions of primary, secondary and tertiary heterocyclic thioamides with alkyl- and arylsulfonyl azides. For each type of thioamides a reliable procedure to prepare N-sulfonyl amidines in good yields was found. Reactions of 1-aryl-1,2,3-triazole-4-carbothioamides with azides were shown to be accompanied with a Dimroth rearrangement to form 1-unsubstituted 5-arylamino-1,2,3-triazole-4-N-sulfonylcarbimidamides. 2,5-Dithiocarbamoylpyridine reacts with sulfonyl azides to form a pyridine bearing two sulfonyl amidine groups.
Keywords: amidines; Dimroth rearrangement; isoxazoles; sulfonyl thiazoles; thioamides; 1,2,3-triazoles

(untitled) - Wu, S.-M.; Qiu, X.-Y.; Liu, S.-J.; Sun, J. (Mini-Rev. Med. Chem., 2020)

PCT Int. Appl. - Wang, Z.; Ma, J.; Li, N.; Li, L. (Preparation of heterocyclic compounds as inhibitors of fibroblast growth factor receptor, 2020)

(untitled) - Lather, A.; Sharma, S.; Khatkar, S.; Khatkar, A. (Curr. Pharm. Des., 2020)

PCT Int. Appl. - Li, D.; Duan, L.; Zheng, T.; Wang, Y.; Jin, K.; Su, W.; Hong, Y.; Xu, J.; Xia, G.; Ke, Y. (Preparation of nitrogen-containing heterocyclic compounds as p38 protein kinase inhibitors, 2020)

(untitled) - Li, X.; Zhang, S.-Q.; Xu, L.-C.; Hong, X. (Angew. Chem., Int. Ed., 2020)

(untitled) - Evano, G.; Blanchard, N.; Toumi, M. (Chem. Rev., 2008)

(untitled) - Patil, N. T.; Yamamoto, Y. (Chem. Rev., 2008)

(untitled) - Whitehouse, M. W. (Curr. Med. Chem., 2005)

(untitled) - Zhou, Q.-F.; Ge, F.-F.; Chen, Q.-Q.; Lu, T. (RSC Adv., 2016)

Comprehensive Heterocyclic Chemistry I - Katritzky, A. R.; Rees, C. W. (Pergamon Press, 1984)

Comprehensive Heterocyclic Chemistry II - Katritzky, A. R.; Rees, C. W.; Scriven, E. F. (Elsevier, 1996)

Comprehensive Heterocyclic Chemistry III - Katritzky, A. R.; Ramsden, C.; Scriven, E. F. V.; Taylor, R. (Elsevier, 2008)

(untitled) - Lee, M. Y.; Kim, M. H.; Kim, J.; Kim, S. H.; Kim, B. T.; Jeong, I. H.; Chang, S.; Kim, S. H.; Chang, S.-Y. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Beryozkina, T.; Bakulev, V.; Dianova, L.; Berseneva, V.; Slepukhin, P.; Leban, J.; Kalaba, P.; Aher, N. Y.; Ilic, M.; Sitte, H. H.; Lubec, G. (Synthesis, 2016)

(untitled) - Rupakova, N. A.; Bakulev, V. A.; Knippschild, U.; García-Reyes, B.; Eltsov, O. S.; Slesarev, G. P.; Beliaev, N.; Slepukhin, P. A.; Witt, L.; Peifer, C.; Beryozkina, T. V. (ARKIVOC, 2017)

(untitled) - Suja, T. D.; Divya, K. V. L.; Naik, L. V.; Kumar, A. R.; Kamal, A. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Scholz, T. H.; Sondey, J. M.; Randall, W. C.; Schwam, H.; Thompson, W. J.; Mallorga, P. J.; Sugrue, M. F.; Graham, S. L. (J. Med. Chem., 1993)

(untitled) - Deprez, P.; Heckmann, B.; Corbier, A.; Vevert, J.-P.; Fortin, M.; Guillaume, J. (Bioorg. Med. Chem. Lett., 1995)

(untitled) - Heitsch, H.; Becker, R. H. A.; Kleemann, H.-W.; Wagner, A. (Bioorg. Med. Chem., 1997)

(untitled) - Bekhit, A. A.; Ashour, H. M. A.; Abdel Ghany, Y. S.; Bekhit, A. E.-D. A.; Baraka, A. (Eur. J. Med. Chem., 2008)

(untitled) - Song, Z.-L.; Chen, H.-L.; Wang, Y.-H.; Goto, M.; Gao, W.-J.; Cheng, P.-L.; Morris-Natschke, S. L.; Liu, Y.-Q.; Zhu, G.-X.; Wang, M.-J.; Lee, K.-H. (Bioorg. Med. Chem. Lett., 2015)

(untitled) - Filimonov, V. O.; Dianova, L. N.; Galata, K. A.; Beryozkina, T. V.; Novikov, M. S.; Berseneva, V. S.; Eltsov, O. S.; Lebedev, A. T.; Slepukhin, P. A.; Bakulev, V. A. (J. Org. Chem., 2017)

(untitled) - Yavari, I.; Ahmadian, S.; Ghazanfarpur-Darjani, M.; Solgi, Y. (Tetrahedron Lett., 2011)

(untitled) - He, X.; Shang, Y.; Hu, J.; Ju, K.; Jiang, W.; Wang, S. (Sci. China: Chem., 2012)

(untitled) - Yang, T.; Cui, H.; Zhang, C.; Zhang, L.; Su, C.-Y. (Inorg. Chem., 2013)

(untitled) - Bae, I.; Han, H.; Chang, S. (J. Am. Chem. Soc., 2005)

(untitled) - Kim, J.; Stahl, S. S. (J. Org. Chem., 2015)

(untitled) - Hwang, S. J.; Cho, S. H.; Chang, S. (Pure Appl. Chem., 2008)

(untitled) - Yoo, E. J.; Ahlquist, M.; Bae, I.; Sharpless, K. B.; Fokin, V. V.; Chang, S. (J. Org. Chem., 2008)

(untitled) - Kim, J.; Lee, S. Y.; Lee, J.; Do, Y.; Chang, S. (J. Org. Chem., 2008)

(untitled) - Krstulović, L.; Ismaili, H.; Bajić, M.; Višnjevac, A.; Glavaš-Obrovac, L.; Žinić, B. (Croat. Chem. Acta, 2012)

(untitled) - Filimonov, V. O.; Dianova, L. N.; Beryozkina, T. V.; Mazur, D.; Beliaev, N. A.; Volkova, N. N.; Ilkin, V. G.; Dehaen, W.; Lebedev, A. T.; Bakulev, V. A. (J. Org. Chem., 2019)

(untitled) - Aswad, M.; Chiba, J.; Tomohiro, T.; Hatanaka, Y. (Chem. Commun., 2013)

(untitled) - Fleury, L. M.; Wilson, E. E.; Vogt, M.; Fan, T. J.; Oliver, A. G.; Ashfeld, B. L. (Angew. Chem., Int. Ed., 2013)

(untitled) - DeKorver, K. A.; Johnson, W. L.; Zhang, Y.; Hsung, R. P.; Dai, H.; Deng, J.; Lohse, A. G.; Zhang, Y.-S. (J. Org. Chem., 2011)

(untitled) - Chen, S.; Xu, Y.; Wan, X. (Org. Lett., 2011)

(untitled) - Chandna, N.; Chandak, N.; Kumar, P.; Kapoor, J. K.; Sharma, P. K. (Green Chem., 2013)

(untitled) - Gobis, K.; Foks, H.; Sławiński, J.; Sikorski, A.; Trzybiński, D.; Augustynowicz-Kopeć, E.; Napiórkowska, A.; Bojanowski, K. (Monatsh. Chem., 2013)

(untitled) - Himbert, G.; Schwickerath, W. (Liebigs Ann. Chem., 1984)

(untitled) - van Loevezijn, A.; Venhorst, J.; Iwema Bakker, W. I.; de Korte, C. G.; de Looff, W.; Verhoog, S.; van Wees, J.-W.; van Hoeve, M.; van de Woestijne, R. P.; van der Neut, M. A. W.; Borst, A. J. M.; van Dongen, M. J. P.; et al. (J. Med. Chem., 2011)

(untitled) - Dianova, L.; Berseneva, V.; Beryozkina, T.; Efimov, I.; Kosterina, M.; Eltsov, O.; Dehaen, W.; Bakulev, V. (Eur. J. Org. Chem., 2015)

(untitled) - Il’kin, V. G.; Berseneva, V. S.; Slepukhin, P. A.; Bakulev, V. A. (Chem. Heterocycl. Compd., 2018)

(untitled) - Shafran, Y.; Glukhareva, T.; Dehaen, W.; Bakulev, V. (Adv. Heterocycl. Chem., 2018)

The Chemistry of 1,2,3-Thiadiazoles - Bakulev, V. A.; Dehaen, W. (John Wiley & Sons, Inc., 2004)

(untitled) - Berseneva, V. S.; Morzherin, Y. Y.; Dehaen, W.; Luyten, I.; Bakulev, V. A. (Tetrahedron, 2001)

(untitled) - Denisova, A. B.; Sosnovskikh, V. Y.; Dehaen, W.; Toppet, S.; Van Meervelt, L.; Bakulev, V. A. (J. Fluorine Chem., 2002)

(untitled) - Bel'skaya, N. P.; Demina, M. A.; Sapognikova, S. G.; Fan, Z.-J.; Zhang, H.-K.; Dehaen, W.; Bakulev, V. A. (ARKIVOC, 2008)

(untitled) - Watkinson, M. (Top. Heterocycl. Chem., 2012)

(untitled) - Belskaya, N.; Subbotina, J.; Lesogorova, S. (Top. Heterocycl. Chem., 2014)

(untitled) - Bakulev, V.; Dehaen, W.; Beryozkina, T. (Top. Heterocycl. Chem., 2015)

(untitled) - Bakulev, V. A.; Tarasov, E. V.; Morzherin, Y. Y.; Luyten, I.; Toppet, S.; Dehaen, W. (Tetrahedron, 1998)

(untitled) - Khazhieva, I. S.; Glukhareva, T. V.; El’tsov, O. S.; Morzherin, Y. Y.; Minin, A. A.; Pozdina, V. A.; Ulitko, M. V. (Pharm. Chem. J., 2015)

(untitled) - Kang, T.; Kim, H.; Kim, J. G.; Chang, S. (Chem. Commun., 2014)

(untitled) - Ilkin, V. G.; Dianova, L. N.; Bakulev, V. A.; Berseneva, V. S.; Saveliev, D. A.; Beryozkina, T. V. (Chem. Heterocycl. Compd., 2020)

(untitled) - Bakulev, V. A.; Beryozkina, T. A. (Chem. Heterocycl. Compd., 2016)

Comprehensive Heterocyclic Chemistry III - Dehaen, W.; Bakulev, V. A. (1,2,3,4-Thiatriazoles, 2008)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

(untitled) - Palatinus, L.; Chapuis, G. (J. Appl. Crystallogr., 2007)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)